Justification by faith alone Affirming the doctrine by which the church and the individual stands or falls - MacArthur, John F., Jr, 1939-; Sproul, Robert Charles; Kistler, Don (Morgan, PA Soli Deo Gloria, 1995)
Includes bibliographical references.
Donated by Mr Doug Wilson, student 1996-1998
Keywords: Faith -- religious aspects -- Christianity